1991
DOI: 10.1597/1545-1569_1991_028_0103_fcodsa_2.3.co_2
|View full text |Cite
|
Sign up to set email alerts
|

Five Cases of DeMyer Sequence: An Interophthalmic Dysplasia

Abstract: Five cases with vomeroseptal-prolabium agenesis, four with premaxillary agenesis, and one with hemipremaxillary agenesis are presented. All five patients had complete clefts of the secondary palate. No known family history for craniofacial dysmorphia was reported. Height and weight ranged from 2nd to 10th centile. Psychological testing showed intelligent quotients of 121, 93, 72 for three patients; two were microcephalic with undetermined IQ, but severe generalized developmental delay. CT scans for the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Ben-Hur et al (1978) described a 12-year-old boy with a median cleft lip, orbital hypotelorism, a normal karyogram, and normal psychomotor development; they concluded that the typical facial dysmorphia and orbital hypotelorism did not necessarily mean holoprosencephaly. They also emphasized the importance of the CT scan, which can offer a valid diagnosis and, in rare cases, could exclude gloomy predictions (Spolyar et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Ben-Hur et al (1978) described a 12-year-old boy with a median cleft lip, orbital hypotelorism, a normal karyogram, and normal psychomotor development; they concluded that the typical facial dysmorphia and orbital hypotelorism did not necessarily mean holoprosencephaly. They also emphasized the importance of the CT scan, which can offer a valid diagnosis and, in rare cases, could exclude gloomy predictions (Spolyar et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…When medial cleft lip occurs without holoprosencephaly, head circumference is within two standard deviations of the mean and normotelorism is usual. 53 An intact ethmoid, nasal bone, and crista galli appear to represent the key anatomical differences in these patients as compared with classic holoprosencephaly (Fig. If the original holospheric telencepha-lon fails to develop lateral evaginations, the cerebrum remains singular rather than hemispheric.…”
Section: Median Cleft Lipmentioning
confidence: 95%